Pedro Augusto Motta: Militância Libertária e Verbo de Fogo - Braga, Francisco Victor Pereira (2013)
The present research covers the militant trajectory of the anarchist Pedro Augusto Motta, whose life is marked by significant sociopolitical acting in Brazil during the first decades of the 20th century. On studying the dimensions of his militant life, it is discussed the labor movement, the anarchism and its militancy articulately, particularly in the cities Fortaleza and São Paulo. Analyzing the trajectory of such a character and his dialogue with the militant experiences in his time, within the ambit of the anarchist practices and sociabilities over a span between 1894 and 1927, this work discusses the circulation of new ideas which situated the typographer Pedro Augusto Motta in relation to a generation of young militant and workers of various crafts, in Fortaleza, as well as his adherence to resistance syndicalism, militant writing on anarchist press and anarchist and revolutionary syndicalism propaganda. It also highlights his militancy in São Paulo, where he became member of Centro Libertário Terra Livre and part of the editor group of A Plebe newspaper. Considering the context of intense repression in the early twenties, the study also deals with the prison and deportation of Pedro Augusto Motta to a concentration camp in Clevelândia do Norte, Oyapoque, Amazon forest.